2022
DOI: 10.3847/2041-8213/aca675
|View full text |Cite
|
Sign up to set email alerts
|

Early JWST Imaging Reveals Strong Optical and NIR Color Gradients in Galaxies at z ∼ 2 Driven Mostly by Dust

Abstract: Recent studies have shown that galaxies at cosmic noon are redder in the center and bluer in the outskirts, mirroring results in the local universe. These color gradients could be caused by gradients in either the stellar age or dust opacity; however, distinguishing between these two causes is impossible with rest-frame optical photometry alone. Here we investigate the underlying causes of the gradients from spatially resolved rest-frame U − V versus V − J color–color diagrams measured from early observations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
(89 reference statements)
1
8
0
Order By: Relevance
“…Distinctively, quiescent galaxies are composed of regions with A(V ) < 1 mag dust attenuations, the median being around 0.3 mag. The regions with the highest attenuations are preferentially located in the inner 2 kpc, or 2 × r e,M , with a significant gradient toward larger radii, similar to what has been reported at lower redshifts (see Wang et al 2017;Miller et al 2022), but with larger nuclear attenuations in the case of SMGs (compared to main-sequence galaxies at z ∼ 2; see, e.g., Tacchella et al 2018). XELG-z6 present a quite flat attenuation distribution, which extends from unobscured to A(V) = 3 mag, i.e., the starburst we see as an emission line is also dusty, but these are very compact sources, as we mentioned earlier.…”
Section: Spatially Resolved Analysis Of the Stellar Populationssupporting
confidence: 76%
“…Distinctively, quiescent galaxies are composed of regions with A(V ) < 1 mag dust attenuations, the median being around 0.3 mag. The regions with the highest attenuations are preferentially located in the inner 2 kpc, or 2 × r e,M , with a significant gradient toward larger radii, similar to what has been reported at lower redshifts (see Wang et al 2017;Miller et al 2022), but with larger nuclear attenuations in the case of SMGs (compared to main-sequence galaxies at z ∼ 2; see, e.g., Tacchella et al 2018). XELG-z6 present a quite flat attenuation distribution, which extends from unobscured to A(V) = 3 mag, i.e., the starburst we see as an emission line is also dusty, but these are very compact sources, as we mentioned earlier.…”
Section: Spatially Resolved Analysis Of the Stellar Populationssupporting
confidence: 76%
“…The color gradients in our sample are consistent with the idea of looking through large dust columns at all radii in edge-on disks. A more in-depth discussion of the physical drivers of color gradients (or lack thereof) is presented in Miller et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…As we point out later in this section, this could also be the result of inclination effects. Recently, Miller et al (2022) found that 70% of star-forming galaxies at z ∼ 2 demonstrated U − V/V − J color gradients caused primarily by gradients in dust attenuation (also Liu et al 2017;Wang et al 2017). For the same sample, 23% of the objects showed color gradients that were in line with gradients in stellar population properties (such as specific SFR).…”
Section: A Dust-obscured Nucleus or Inside-out Growth-or Both?mentioning
confidence: 97%
“…The available photometric coverage helps to break the degeneracy between reddening stellar population age versus that from dust attenuation, in particular through the wellstudied UVJ diagram (e.g., Labbé et al 2005;Wuyts et al 2007;Patel et al 2012). The F115W, F150W, and F200W filters together offer strong constraints on the rest-frame U and V fluxes, while F356W now offers comparable spatialresolution coverage of rest-frame J flux for the first time (Miller et al 2022). As discussed by Leja et al (2019), however, SEDfitting is often more precise and accurate than color-color diagrams in identifying properties.…”
Section: Inner Versus Outer Disk Decompositionmentioning
confidence: 99%